The legacy of liberal Judaism : Ernst Cassirer and Hannah Arendt's hidden conversation - Curthoys, Ned (Berghahn, 2013)
'This man of our destiny': Moses Mendelssohn, Nathan the Wise, and the emergence of a liberal Jewish ethos -- Diasporic visions: the emergence of liberal Judaism -- Abraham Geiger -- Hermann Cohen's prophetic Judaism -- Ernst Cassirer and the ethical legacy of Hermann Cohen -- Ernst Cassirer: the enlightenment as counter-history -- Hannah Arendt: the task of the historian -- Hannah Arendt: a question of character